Correlation Of Vitamin D Levels With Inflammatory Cytokines In Autoimmune Disorders - Fatima, Yamna; Majeed, Sana; Rehman, Madiha; Anwar, Sidra; Zaidi, Mehreen; Niazi, Zehra (Journal of Neonatal Surgery, 2025)
Background: Vitamin D is a very important immunomodulator and it is also considered to play an important role in control of immune responses. Its low levels in autoimmune diseases are associated with increased inflammation, which is usually further augmented by the increased pro-inflammatory cytokines. The link between vitamin D and the levels of inflammatory cytokines may reveal the way the disease advances and what means may be used to treat the patient. Objectives: Aim of Study to determine the correlation of vitamin D and inflammatory cytokines in autoimmune patients. Study design: A cross-sectional study. Place and duration of study: Department of Physiology, Central Park Medical College, Lahore, Pakistan from March 2024 to October 2024. Methods: Cross-sectional study was carried out among the patients with autoimmune disorders. The levels of serum vitamin D .and the concentration of cytokines (IL-6, TNF-alpha, IL-10) were determined. The relationship between cytokine levels and vitamin D insufficiency was determined using statistical analysis (selection of vitamin D insufficiency and association of any correlation and t-tests). Results: They have analyzed a total of 100 patients with a mean of 40.6 years of age (SD = 12.4). Low concentration of vitamin D was associated positively with various pro-inflammatory cytokines such as IL-6, TNF-a, and IL-1-b (p < 0.01). On the contrary, the cytokine levels were lower in patients with high levels of vitamin D. The information indicated that insufficiency of vitamin D increases inflammation in autoimmune diseases. Conclusion: Human autoimmune disorders are demonstrated to have elevated inflammatory cytokines in the condition of vitamin D deficiency. It is possible that supplementation can control inflammation and control the course of disease but more study needs to be conducted to determine effective doses in terms of clinical practice.